Silicon and phosphorus impacts on seasonal nutrient dynamics and tree performance of citrus sinensis L. under endemic Huanglongbing conditions - Fajardo, Jose Luis Prieto; Souza Junior, Jonas Pereira de; Shahid, Muhammad A.; Hammond, William; Diepenbrock, Lauren; Kadyampakeni, Davie M. (Frontiers in Plant Science, 2025)
IntroductionUnder endemic Huanglongbing (HLB) conditions, optimizing nutrient management in citrus production is crucial to mitigate disease-related disruptions in nutrition uptake and improve citrus tree health and productivity.MethodsThis study evaluated the influence of foliar-applied silicon (Si) and soil-applied phosphorus (P) on the seasonal nutrient dynamics of Valencia sweet orange (Citrus sinensis) leaves. The experiment was conducted in a mature orchard over five seasons using three Si application rates (3.75, 7.50, and 11.25mg per plant) in two P fertilization levels (15.63 and 31.26 g P per plant). Leaf samples were collected seasonally and analyzed for macronutrient and micronutrient concentrations. Horticultural parameters such as trunk cross sectional area (TCSA) and total canopy volume (TCV) were also measured.ResultsSeasonal variation was the primary driver of leaf nutrient concentrations, with Summer generally favoring higher accumulation of nitrogen, potassium, calcium, and iron. Silicon application showed greater benefits under low P availability, particularly at the low rate (3.75 mg per plant), which improved the accumulation of key nutrients such as magnesium and enhanced TCSA. Under high P conditions, the effects of Si were more variable, with limited or inconsistent impacts on nutrient uptake.DiscussionHierarchical clustering analysis revealed that Si contributed to distinct nutrient grouping patterns and influenced the multivariate nutrient network, particularly under P-limiting conditions. These findings demonstrated the context-dependent nature of Si efficacy and emphasize the importance of optimizing both the rate and timing of application.ConclusionThe study provides evidence that foliar Si application can support nutrient acquisition and plant development in citrus, especially in a low P availability scenario. Integrating Si into nutrient management programs may enhance the resilience and productivity of citrus trees under variable environmental and soil fertility conditions especially under the endemic conditions of citrus greening in Florida.